ANALISIS PENGUASAAN KATA SINONIM“TONGYANG”DAN “YIYANG” PADA MAHASISWAANGKATAN 2017 PENDIDIKAN BAHASA MANDARIN - Novia Panca Satriani; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2019)
AbstractSynonyms are words that has the same meaning. “tongyang” and “yiyang” are meant synonyms. These two words are often used in daily life. Judging from the meaning of the meaning of the word and its use, there are similarities and difference between these two words. Therefore, students often do errors in using these two words. In order to understand the mastery condition of Mandarin Education Study Program FKIP UNTAN 2017 students toward mastery of the synonym words “tongyang” and “yiyang”, the writer used a test method to examine students understanding and difficulties of the synonym “tongyang” and “yiyang”. The results of the study stated that the mastery of students in the synonym “yiyang” was better than “tongyang”. The percentage of correct answers for the word “tongyang” is 64% and the percentage of correct answers for the word “yiyang” is 82%. In the analysis of the types of difficulties, the writer realized that students lack mastery in the use of the word “tongyang” with the beginning sentence and the use of the word “yiyang” can indicate as a predicate. Keywords: Synonym Word, Tongyang and yiyang, Condition of Mastery